Evaluating the coal rebound effect in energy intensive industries of China. (15th September 2020) - Wei, Wei; Mushtaq, Zulqarnain; Sharif, Maimoona; Zeng, Xiaowu; Wan-Li, Zhang; Qaisrani, Mumtaz A.
Abstract: The energy intensive industries of China consumes the highest share of coal that accounts for 93.69% of China's total coal consumption. Hence, these industries are important to achieve the goals to reduce carbon emission and energy conservation. The LMDI decomposition analysis is used to investigate the factors affecting coal consumption in these industries. The empirical findings indices that first, gross industrial output and structural changes had accelerated coal consumption, whereas energy intensity de-accelerated coal consumption. Second, technological improvements boosted industrial growth rate. Finally, results also reveal that there exists a coal rebound effect in energy intensive industries with the maximum at 35.07% in 2016, with an increasing trend during 1990–2016. The present research can help the policymakers to design a pinpointed policy framework to reduce carbon emission and coal conservation. Highlights: The coal rebound effect is evaluated by applying a well-designed mechanism. LMDI model is applied to decompose the total coal consumption. The technological indicator is estimated by using the resource intensity method. Coal intensity deaccelerated, while output growth accelerated coal consumption. Coal rebound effect is estimated as 35.07% in China's energy intensive industries.